Exploring Intensive Longitudinal Measures of Student Engagement in Blended Learning - Henrie, Curtis R; Bodily, Robert; Manwaring, Kristine C; Graham, Charles R (International Review of Research in Open and Distributed Learning, 2015)
In this exploratory study we used an intensive longitudinal approach to measure student engagement in a blended educational technology course, collecting both self-report and observational data. The self-report measure included a simple survey of Likert-scale and open-ended questions given repeatedly during the semester. Observational data were student activity data extracted from the learning management system. We explored how engagement varied over time, both at the course level and between students, to identify patterns and influences of student engagement in a blended course. We found that clarity of instruction and relevance of activities influenced student satisfaction more than the medium of instruction. Student engagement patterns observed in the log data revealed that exploring learning tools and previewing upcoming assignments and learning activities can be useful indicators of a successful learning experience. Future work will investigate these findings on a larger scale.